THE EFFECT OF THE HEAVY RECREATIONAL TRAFFIC ON THE DESIGN OF THE FREEWAY (Iraqi Journal of Civil Engineering, 2008)
Traffic engineers frequently are engaged in evaluating the performance of different facilities of the highway system. The facility in this project includes freeway section. In design of a freeway, a forecast demand volume is used with known design standards for geometric features and a desired level of service to compute the number of lanes required for the freeway section in question. The design application is straight forward for each usage, but trial-and- error operation analysis may be required to evaluate alternative design. Design requires a detailed traffic forecast, including volumes, peaking characteristics, traffic composition, and specifics of vertical and horizontal alignment for the section under study. The aim of this paper is the design analysis of a freeway with a heavy recreational vehicles. This analysis involves the consideration of three examples of freeways. Given known geometric roadway conditions and projected traffic conditions , the design analysis yields an estimation of the number of lanes and of the speed and density of the traffic stream. This paper has described the procedure for determining the number of lanes of freeway basic sections as presented in the Highway Capacity Manual (HCM, 2000) and HCS2000 software.